Utilizing open-ended approach to enhance mathematical understanding among vocational high school students - Rifai, Rusdian; Turmudi; Jarnawi Afgani Dahlan; Suhendra (Universitas Hamzanwadi, 2025)
Mathematics learning in vocational high schools is still teacher-centred and relies on structured exercises, leaving little room for students to develop a conceptual understanding. The open-ended approach can be a solution because it allows students to explore various strategies for solving mathematical problems in depth. However, its implementation in vocational high schools remains limited. This study aimed to examine the effectiveness of the open-ended approach in improving the mathematical understanding of vocational high school students. A quasi-experimental design with a pretest-posttest control group design was used. The sample consisted of 72 students in the 11th-grade of Computer and Network Engineering, selected based on previously formed classes. Data were obtained through a mathematical understanding test that measured students' ability to identify, use, and apply the concepts of sequences and series to solve everyday problems. The test instrument consisted of three essay questions, with a maximum score of four for each item. As the data were not normally distributed, the Mann-Whitney U test analysis was used. The results showed that the increase in mathematical understanding of the group of students who received the open-ended approach was significantly better than that of the group who received direct learning.